HUBUNGAN POLA ASUH IBU DENGAN PERKEMBANGAN MENTAL EMOSIONAL PADA ANAK PRASEKOLAH DI PAUD SAKINAH LUMAJANG - Frilasari, Heni; Zuhriyah, Isfi (Jurnal Keperawatan Bina Sehat, 2012)
Each mother has different parenting styles, because of differences in perception. Not only physical growth but parents must also consider the development mental and emotional of children. Parenting is very influential in the formation of personality and personality-forming aspects are: emotional, social, motivational, intellectual and spiritual. This type of research analytical correlation. Its population is all mothers with preschool children in PAUD Sakinah Lumajang with sample of 32 respondents. This research uses total sampling techniques. The instrument used was KMEE and keusioner. The data collected were then tested with the Contingency Coefficient. The results of this research indicate that most respondents apply the democratic parenting style that is 16 respondents (50%) smaller apply permissive parenting is 9 respondents (28%). Almost half the respondents did not experience emotional mental problem that is 12 respondents (38%). Having tested using the contingency coefficient test with significance level α value: 0.05. The test results obtained value of contingency coefficient 0.000 <0.05, so that H0 is rejected and H1 accepted which means there is a relationship of parenting mother to mental emotional on preschoolers in PAUD Sakinah Lumajang. Meanwhile, if seen from the closeness of the relationship of 0.626 means the relationships in the category of firmly. This research proves that parenting style is very democratic established of mental and emotional well. Parents are in demand to give control of growth and development in order to reach mature adulthood.Keywords: parenting, mental, emotional, preschoolers